PENGEMBANGAN OLAHRAGA TRADISIONAL HADANG BERBASIS MEDIA BOLA KAIN PADA SISWA KELAS V di SDN 1 SUKAMULYA - Febrianti, Elma Sita; Sartono, Sartono (STKIP Melawi, 2025)
Abstract: Development of the Traditional Hadang Game Based on Cloth Ball Media, Class V student of SDN 1 Sukamulya. The method used in this research is the research and development method (Research and Development). Development research methods are used to produce new product designs. This research was conducted to develop learning media, namely cloth balls, and change the steps of the previous hadang game into a traditional game of hadang based on cloth ball media. The author uses the ADDIE research model (Analysis, Design, Development, implementation and evaluation) which has five stages. The products produced are cloth ball media and the latest steps for the game of cloth ball media-based game. This product was implemented for 21 class V students at SDN 1 Sukamulya. After implementation there are results before and after implementation where the results show that the students' agility abilities in the Preetest results have an average (mean) of 7.81 and the preetest results have an average or (mean) value of 11.33 after being given treatment ( treetment) and the result of (2-tailed) with a value of 0.000. Therefore, if the significance value is smaller than the basic formula for taking it (0.000<0.05), it can be concluded that the traditional game of hadang based on cloth balls is effective for improving students' agility abilities.Keywords: Game, Agility, Cloth Ball BasedÂ Abstrak: Metode yang digunakan dalam penelitian ini adalah metode penelitian pengembangan (Research and Development). Penelitian ini dilakukan untuk mengembangkan media pembelajaran yaitu bola kain dan merubah langkah-langkah permainan hadang terdahulu dirubah menjadi permainan tradisonal hadang berbasis media bola kain. Penulis menggunakan model penelitian ADDIE (Analysis, Design, Development,implementation dan evaluasion) yang mana terdapat lima tahapan. Produk yang dihasilkan yaitu media bola kain dan keterbaruan langkah-langkah permainan hadang berbasis media bola kain. Produk ini di implementasikan pada siswa kelas V SDN 1 Sukamulya yang berjumlah 21 orang. Setelah penerapan terdapat hasil sebelum dan sesudah penerapan yang mana hasilnya menunjukan bahwa kemampuan kelincahan siswa pada hasil Pretest memiliki rata-rata (mean) sebesar 7,81 dan hasil pretest memiliki nilai rata-rata atau (mean) sebesar 11,33 setelah diberikan perlakuan (tretment) dan hasil dari (2-tailed) dengan nilai 0,000. Maka dari itu, apabila nilai signitifikasi lebih kecil dari rumus dasar pengambilan (0,000<0,05) maka dapat disimpulkan permainan tradisional hadang berbasis media bola kain efektif untuk meningkatkan kemampuan kelincahan siswa.Kata Kunci: Permainan, olahraga tradisional hadang, Bola Kain